High-frequency oscillatory ventilation: still a role?. Issue 2 (April 2017) - Ng, Jensen; Ferguson, Niall D.
Abstract : Purpose of review: In light of emerging data from clinical trials, the place of high-frequency oscillatory ventilation (HFOV) in the management of acute respiratory distress syndrome (ARDS) is uncertain. This review provides an overview of these new clinical data and also explores new areas of investigation for HFOV in adults. Recent findings: While prior meta-analyses suggested benefit for HFOV, updated systematic reviews published this year, which include two large recent clinical trials, now show no statistically significant impact of HFOV on mortality in adults with ARDS. It is possible that HFOV would be safer and more effective with a more individualized approach to setting mean airway pressure (mPaw). Possible techniques to achieve this include titrating mPaw in response to oxygenation or hemodynamic changes after HFOV initiation, by measuring respiratory system impedance, or by following echocardiographic changes. Summary: Although not first-line, HFOV remains a tool in the armamentarium of the intensivist managing the patient with severe ARDS and refractory hypoxemia. A refinement in the approach to delivering HFOV is warranted, with more attention paid to its adverse hemodynamic consequences.